Pelestarian Kearifan Lokal Kain Tradisional Gambo: Upaya Meningkatkan Kualitas Hidup Dan Kebudayaan Masyarakat - Marsinah Marsinah; R.A Rodia Fitri Indriani; Hatidah Hatidah; M Bambang Purwanto (Jurnal Kabar Masyarakat, 2024)
The community service program with the theme "Preservation of Local Wisdom of Gambo Traditional Fabrics: Efforts to Improve the Quality of Life and Community Culture" was carried out by lecturers from the Prasetiya Mandiri Polytechnic in Babat Toman Village, Musi Banyuasin Regency. This activity aims to preserve Gambo traditional fabrics while improving the quality of life and culture of the local community. In one day of implementation, this program involved various activities such as training on Gambo fabric making techniques, innovative design workshops, and discussion sessions on business management and marketing strategies. Through this training, local artisans gain new knowledge about jumputan techniques and creative design, as well as insights into the use of digital platforms for product marketing. The results of this activity showed a significant increase in the knowledge and skills of participants, strengthening the capacity of local artisans, and the formation of a collaborative network between craftsmen, village governments, and educational institutions. In addition, this program succeeded in raising awareness of the importance of preserving local wisdom as a valuable cultural identity. Overall, this program has succeeded in achieving its goals and has a significant positive impact on the people of Babat Toman Village. With recommendations for continuous training and wider market access support, it is hoped that Gambo traditional fabrics can continue to be preserved and become a sustainable source of livelihood for the local community.